Effect of Different Medium on Survival Rate and Growth of Chironomus sp. Larvae - . Widanarni; D.D. Mailana; O. Carman (Jurnal Akuakultur Indonesia)
In the ornamental fish and fish for food culture, feeding by natural feed is very suitable since they are easy to digest and their size is suitable with  to larval mouth.  One of natural foods is blood worm Chironomus sp. larvae that has high protein content (till  65.2% of  protein). Until now, blood worm is obtained from nature and their stock depends on the weather.  That problem  may be overcome by culturing blood worm in appropriate culture medium.  Naturally, Chironomus sp. grows well in the water containing sago waste.  This study was carried out to examine the growth of Chironomus sp. reared in the medium containing mud, solid sago waste, solid tapioca wastes and water with no waste in depth of 0.5 cm. After 35-day rearing, survival rate of Chironomus sp was different among the treatments, while growth in length was similar. The best survival rate, 58.93% was obtained in the media containing solid sago waste.